Analisis Kinerja Reksa Dana Saham Di Indonesia - Muhammad Ikhsan; Hurriah Ali Hasan (Jurnal Ekonomi dan Bisnis Digital, 2023)
Mutual fund is a company who invest in a variety of stock portfolio managed by an investment manager. Many investors have less knowledge and experience in forming optimal portfolios, especially regarding indicators that affect the performance of mutual funds. This study aims to analyze the performance of mutual fund shares affected by asset allocation policy, investment manager performance and the size of the mutual fund which was conducted at the mutual fund shares registered in Bapepam - LK 2008-2012 by using multiple linear regression analysis techniques. The results showed that asset allocation policy have negative and significant effect on the performance of mutual funds, investment manager performance have positive and significant effect on the performance of equity funds, and the size of mutual funds positive and significant effect on the performance of mutual fund shares.